Penerapan Teknologi Augmented Reality sebagai Sarana Promosi Produk Sarana Sejahtera Wilson’s Office Chairs Berbasis Android - Rachel Chrysilla Tijono; R. Rizal Isnanto; Kurniawan Teguh Martono (Jurnal Teknologi dan Sistem Komputer, 2015)
Nowadays, business competitions become much fiercer, whether it be small, medium, or large business. It even makes many enterpreuners go out of business because they took the wrong step facing the fierce competition. A precise strategy is needed to face the competition, such as knowing the location of the costumers,knowing the needs of the costumers, utilizing the surroundings, utilizing technologies, etc. Simple selling products such as adding pictures of the produts in brochures is considered less interesting for costumers. By utilizing Augmented Reality technology for product presentation, businessmen are expected to present more interesting products promotion to the costumer and achieve higher sale value. The application of Augmented Reality technology for promoting products is built by SDLC (Software Development Life Cycle) method consist of Concepting, Desaigning, Collecting Materials, Making, Examination, and Distribution steps. The Examination steps uses Black-Box Testing method that consists of Application Functionality test, Lighting Intensity test, Angle and Length of The Camera from the marker. Based on the examination and analysis results towards the built application, it is concluded that application utilization can be a product advertising in the form of Personal Selling. Light intensity affects camera’s perception on Marker’s ID. In the 90 ̊ angle, the detection is nonoptimal because system can’t perceive the marker ID completely. Functionally, all buttons are functioning well and all the pages are openable.